The relationship between different interleukins and T helper cells count in patients with immune thrombocytopenia - Li, Yuru; Hou, Chuandong; Yan, Wenjing; Li, Xiaoxia; Deng, Xinli (Cellular and Molecular Biology, 2022)
Immune thrombocytopenia is the most common autoimmune disorder involving blood types. In several studies, the role of T CD4+ cells in patients with immune thrombocytopenia has been associated with different results. Therefore, in this study, with the aim of applied research in the pathogenesis of immune thrombocytopenia, the relationship was investigated between the number of T CD4+ cells, serum levels of IL-11 and IL-17 cytokines, and platelet count. In this regard, 100 patients with immune thrombocytopenia and 100 healthy individuals were included in the study. The T CD4+ cell counts were examined by flow cytometry and in addition, serum levels of interleukins 11 and 17 were measured by ELISA. The results of this study showed that the number of T CD4+ cells and plasma level of IL-17 were not significantly different between the two groups, but plasma levels of IL-11 in the patient group were significantly higher than the control group (P = 0.286). Overall, in this study, the level of cytokine IL-11 was significantly increased in comparison with IL-17 and T CD4+ cells in patients with immune thrombocytopenia, so it is suggested that measurement of cytokine IL-11 level in these patients could be considered as a critical diagnostic marker and indicator in the stages of disease progression.